MEMPOSISIKAN KEMBALI KEDUDUKAN PEREMPUAN DALAM SUNNAH NABI ANALISIS KRITIS HADIS-HADIS NABI YANG MISOGINIS - Marzuki Marzuki (Jurnal Penelitian Humaniora, 2005)
Abstract The main problems in this research are how the woman status is depicted in prophet hood of Muhammad, how Muhammad’s hadiths posit the woman, and why the mysogyny hadiths emerges. Therefore,  the aims of this research are to explore an to find the answers of the problems above. The research uses content analysis approach. The object of the research is misogynic hadiths that show aversion to women. The selected hadiths are those which become the basis of ulama’s arguments about the position of women. The result of the research shows that, in general, the depiction of woman in Prophet’s hadiths tends to be different from that in Quran. It can be seen from ulama’s understanding that there is an imbalance position is a  lower than men’s.  the view is strengthened by misogynic hadiths showing dislike to women. Studying the problem with different approach from what ulama believe, the misogynic hadiths do not mean as what the ulama interpret. Using metaphoric (majazi) and contextual approach. Contextual approach puts the hadiths in its place, with the more appropriate meanings. Keywords: hadiths, misogyny, contextual